2009
DOI: 10.1039/b909521g
|View full text |Cite
|
Sign up to set email alerts
|

Statistical approaches used to assess and redesign surface water-quality-monitoring networks

Abstract: An up-to-date review of the statistical approaches utilized for the assessment and redesign of surface water quality monitoring (WQM) networks is presented. The main technical aspects of network design are covered in four sections, addressing monitoring objectives, water quality variables, sampling frequency and spatial distribution of sampling locations. This paper discusses various monitoring objectives and related procedures used for the assessment and redesign of long-term surface WQM networks. The appropr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
73
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 76 publications
(74 citation statements)
references
References 62 publications
0
73
0
1
Order By: Relevance
“…The validity of this model is verified by SQL Modeler Software, which will be introduced in succession (later) within a Relational Management Data Base System RMDBS under Access [15]. The implementation of PDM under access is followed by the creation of requests and forms that meet the needs of users and investors for the management of water resources.…”
Section: Rmdbsmentioning
confidence: 99%
“…The validity of this model is verified by SQL Modeler Software, which will be introduced in succession (later) within a Relational Management Data Base System RMDBS under Access [15]. The implementation of PDM under access is followed by the creation of requests and forms that meet the needs of users and investors for the management of water resources.…”
Section: Rmdbsmentioning
confidence: 99%
“…Their studies treat the network design problem in a comprehensive and systematic framework, starting with objectives of monitoring and elaborating on various technical design features, e.g., selection of sampling sites, sampling frequencies, variables to be monitored, and sampling duration. Khalil and Ouarda [5] reviewed the statistical approaches utilized for the assessment and redesign of surface water quality monitoring (WQM) networks and Khalil et al [6] explained the various deficiencies in the statistical approaches proposed in the literature for the assessment and redesign of surface WQM locations. Beveridge et al [7] used geostatistical methods to quantify redundancy in an intentionally dense network of lake stations.…”
Section: Introductionmentioning
confidence: 99%
“…The importance of water and its role as essential for human health, animals and plants [1,2] essential for crop and animal production, for aquatic and terrestrial ecosystems [3] and for our daily life supporting activities [4] is well observed . Water of adequate quantity and quality is essential for sustainable development [5].…”
Section: Introductionmentioning
confidence: 99%